The CCN1 (CYR61) protein promotes skin growth by enhancing epithelial‐mesenchymal transition during skin expansion - Zhou, Yiwen (J Cell Mol Med, 2019)
The skin expansion technique is widely used to induce skin growth for large‐scale skin deformity reconstruction. However, the capacity for skin expansion is limited and searching for ways to improve the expansion efficiency is a challenge. In this study, we aimed to explore the possible mechanism of skin expansion and to find a potential therapeutic target on promoting skin growth. We conducted weighted gene coexpression network analysis (WGCNA) of microarray data generated from rat skin expansion and found CCN1 (CYR61) to be the central hub gene related to epithelial‐mesenchymal transition (EMT). CCN1 up‐regulation was confirmed in human and rat expanded skin and also in mechanically stretched rat keratinocytes, together with acquired mesenchymal phenotype. After CCN1 stimulation on keratinocytes, cell proliferation was promoted and partial EMT was induced by activating β‐catenin pathway. Treatment of CCN1 protein could significantly increase the flap thickness, improve the blood supply and restore the structure in a rat model of skin expansion, whereas inhibition of CCN1 through shRNA interference could dramatically reduce the efficiency of skin expansion. Our findings demonstrate that CCN1 plays a crucial role in skin expansion and that CCN1 may serve as a potential therapeutic target to promote skin growth and improve the efficiency of skin expansion.